Functionalization of CNTS with maleic anhydride - Araújo, Rui Filipe (2012)
The outstanding properties of carbon nanotubes (CNTs) [1] are mainly related with their unique structural features. However, the high π-π staking between the tubes is a major drawback for their manipulation and interaction with other materials. Chemical functionalization has been used as a convenient tool to improve their performance in various applications [2]. The work reports the functionalization of multi-wall carbon nanotubes (MWCNTs) with maleic anhydride via a Diels-Alder addition reaction, performed in dimethyl sulfoxide (190 ºC) or 2-chorotoluene (150 ºC) for 24 hours. The product was characterized by thermogravimetric analysis (TGA) and the weight loss at 800 ºC was 11.9 and 3.7 % respectively. Potentiometric titration suggests that CNTs modified at 190 ºC remain predominantly in the anhydride form, while for CNTs modified at 150 ºC, the extent of hydrolysis is approximately 40 %. Maleic anhydride was also reacted with a model compound (anthracene) in dimethyl sulfoxide (190 ºC) and the hydrolysis of the product (0.025 mmol in 650 µL of DMSO-d6) was followed by 1H RMN upon addition of 0.166 mmol of DCl (40 % weight in D2O) (graphic in figure). The anhydride 1 was easily regenerated from the dicarboxylic acid 2 when this compound was heated at 185 ºC for 10 minutes. A similar behavior is expected for the modified CNTs.